Structural health monitoring and modal parameters identification of Mezcala Bridge - Miguel Anaya-Diaz; Francisco J Carrion-Viramontes; Juan A Quintana-Rodriguez; Luis A Martinez-Trujano; Jose M Machorro-Lopez (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2022)
Since 2016 the Instituto Mexicano del Transporte (Mexican Transport Institute) has continuously instrumented and performed the structural monitoring of the Mezcala Bridge, which is a cable-stayed bridge located in the State of Guerrero, Mexico. In order to identify early damage, several monitoring strategies based on changes in the bridge modal parameters have been implemented. To establish the limits of the parameters, such as the natural frequencies, damping ratios, and mode shapes, it is necessary to characterize the bridge dynamic behavior through monitoring information from the last 3 years, in order to analyze statistically every parameter and simulate different real damage scenarios. Modal parameters are calculated and evaluated every week or after accidents, earthquakes, or strong winds. Applying the proposed methodology based on the Enhanced Frequency Domain Decomposition (EFDD), the modal parameters of the Mezcala Bridge were efficiently estimated and monitored and subsequently, they could be used for finite element model development and calibration in order to evaluate the structural integrity of the bridge.